Avatar, the last airbender. Ashes of the academy - Hicks, Faith Erin (Dark Horse Books, 2025)
Kiyi, half-sister to Fire Lord Zuko, enrolls at the strict Royal Fire Academy for Girls, but when a seed of doubt about the new headmistress is planted, Zuko takes action by installing one of the people he trusts most, Mai, as an academy teacher.